ANALISIS PENERAPAN SISTEM BAGI HASIL TABUNGAN EASY MUDHARABAH PADA BANK SYARIAH INDONESIA (PERSERO ) TBK KANTOR CABANG PEMBANTU PARUNG - Indri Damayanti (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2022)
This study aims to analyze how the profit-sharing system according to sharia rules is applied to Easy Mudharabah Savings at Bank Syariah Indonesia. The research method is descriptive and quantitative with the type of case study research on the object under study. Sources of data used include primary data and secondary data. Research data collection was carried out by interviewing the Branch Manager and Marketing of Bank Syariah Indonesia (Persero), Tbk. KCP Parung. The results of the research at Bank Syariah Indonesia (Persero), Tbk. KCP Parung has used the calculation of profit-sharing based on revenue sharing and the contract applied is the Mudharabah Mutlaqah contract. For future developments, Bank Syariah Indonesia (Persero), Tbk. KCP Parung must increase the introduction of products to the public and must be able to take advantage of the strategic location of the office